Faktor Penentu Kinerja Keuangan Perusahaan BUMN Tahun 2019-2023 - Mardiani Gunawan; Merry Susanti (Economic Reviews Journal, 2025)
This study aims to analyze the influence of the Audit Committee, Board Size, Independent Commissioners, and Intellectual Capital on the Financial Performance of banking companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The sample was selected using purposive sampling, with secondary data obtained from annual reports and financial statements available on the official IDX website. Data were processed using SPSS version 26 with a quantitative approach through multiple linear regression analysis to examine the relationship between independent and dependent variables. The results show that the Audit Committee has a significant positive effect on Financial Performance (ROA), while Board Size and Intellectual Capital have a significant negative effect, and Independent Commissioners have no significant effect. The findings highlight the importance of strengthening the role of the audit committee and optimizing intellectual capital as strategies to enhance financial performance, as well as providing insights for investors in considering corporate governance factors when making investment decisions.